INFLUENCE STUDY ON THE LOGO OF AN ENGINE CONNECTING ROD TO ITS FATIGUE STRENGTH - JIA DeWen; SONG Dong; LEI JiLin; DENG Wei; CUI ZhiZhong; ZHANG TaoTao (Jixie qiangdu)
The connecting rod breaked in the logo position at the middle of the connecting rod body, when it was subjected to cyclin load fatigue experiment. The material and manufacturing process of the experimental samples were checked and there was no defect. The three-dimension solid model of the experimental connecting rod was built by 3-D modeling software, and the stress concentration had occurred at the same location logo with the experimental sample connecting rod by using finite element method. Then three schemes were designed and the influence on the distance between the logo words, the height of logo to connecting rod body surface and the positing of the logo to stress were analysis, the results showed that: the stress was reduced by appropriately increasing the spacing between logo words. The depressing logo could greatly reduce the stress comparing with the protruding logo. The positon of the logo had the most influence to the stress, and the stress concentration of the connecting rod disappeared when the logo moved from middle of the connecting rod to the outside of the connecting rod cap.